2017
DOI: 10.1155/2017/4327069
|View full text |Cite
|
Sign up to set email alerts
|

Complex Characteristics of Multichannel Household Appliance Supply Chain with the Price Competition

Abstract: This paper studies the complex characteristics caused by the price competition in multichannel household appliance supply chains. We consider a two-level household appliance supply chain system consisting of a manufacturer with an Internet channel and a retailer with a traditional channel and an Internet channel. Each channel’s price-setting follows the bounded rational decision process in order to obtain the optimal profit or more market share. Considering that the price competition often leads to the demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Bucki and Suchánek [28] focused on the design and optimization of logistics and production. Ma and Lou [29] investigated the complex characteristics caused by the price competition in multichannel household appliance supply chains. They found that a system in a chaotic state will suffer a larger bullwhip effect than a stable system.…”
Section: Supply Chain Cooperation and Optimizationmentioning
confidence: 99%
“…Bucki and Suchánek [28] focused on the design and optimization of logistics and production. Ma and Lou [29] investigated the complex characteristics caused by the price competition in multichannel household appliance supply chains. They found that a system in a chaotic state will suffer a larger bullwhip effect than a stable system.…”
Section: Supply Chain Cooperation and Optimizationmentioning
confidence: 99%
“…(iii) Similar research results: article [6] is excluded as it reports similar research results as in [5]. Thus, it does not contain additional contributions.…”
Section: Inaccuracy In Demand Information Sharing: Systematic Literatmentioning
confidence: 99%
“…Information sharing is an effective collaboration strategy widely analyzed in the supply chain (SC) managementrelated literature, as it improves SC performance and reduces the noxious bullwhip effect [1][2][3][4][5][6]. This phenomenon can be defined as the amplification of order variability upstream in the SC, and it is known to cause excessive inventory, grossly inaccurate demand forecasts, low capacity utilization, and poor customer service level [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Dan et al [ 10 ] constructed a Stackelberg price game model with the strong retailer as the leader, studied the pricing decision process of the supply chain members and analyzed the influence of key channel factors on the scale of the market such as electric channel market scale expansion and dispersible percentage of electric channels. Ma and Lou [ 11 ] studied the complexity of the price competition in the multi-channel household appliance supply chain and found that the system in chaotic state would be more volatile than that in stable state, and the manufacturer’s network channel helped to alleviate the effect of the bullwhip effect. In addition to the study of price strategy, some scholars have studied the problem of inventory and return in multi-channel supply chain [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%